Pengaruh Empowerment, Teamwork dan Self Esteem Terhadap Kinerja Karyawan Pada ACE Hardware Central Park Kuta (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
Employee performance is “the outcome derived from the routine work processes executed by employees while fulfilling their tasks and responsibilities, utilising company standards effectively and efficiently to achieve organisational objectives. This study aims to assess the impact of Empowerment, Teamwork, and Self-Esteem on Employee Performance at ACE Hardware Central Park Kuta. The study's population comprised all employees at ACE Hardware Central Park Kuta, with a sample size of 80 individuals. The non-probability sampling technique employed was saturated sampling. The data analysis method utilised was multiple linear regression analysis. The findings indicate that Empowerment, Teamwork, and Self-Esteem exert a positive and significant influence on Employee Performance. Collectively, Empowerment, Teamwork, and Self-Esteem positively and significantly affect Employee Performance